COUNTER-REFORMATION IN SOCIAL ASSISTANCE POLICY - Oliveira Nunes, Erica Pollyana; Menezes Amicucci, Eliane Marques de [UNESP] (Fundacao Univ Tocantins, 2020)
This article is about the policy of social assistence and the setbacks in social rights that permeate the current conjunture. When understanding the changes in this scenario in relation to social policies in general resulting from the neoliberal model, the high cuts in the budget and the various reductionist actions to guarantee social rights are notorious. The social assistance policy, one of the most affected, was directed by focalist, selective actions. The challenges are diverse for the realization of its services, benefits and basic programs, with weaknesses exposed in the concretization of social rights to the user families. In addition, they have anti-democratic characteristics in response to the demands arising from the multiple expressions of the social issue. Thus, the study is limited to a bibliographic review and a dialogue about the subject in contemporary times.
Keywords: Social Assistance Policy; Neoliberal Counter-Reformation; Reduction of rights